Sistem Kontrol Alat Pengukur Berbasis IoT Menggunakan Fuzzy Tsukamoto Dipertenakan Ayam Broiler Desa Tonsea Lama - Andrianto bala, Cindy P.C Munaiseche, Kristofel Santa (JOINTER : Journal of Informatics Engineering, 2022)
The Internet of Things (IoT) has a way of working, namely, using an argument from programming language algorithms that have been made and well structured. Each argument that has been formed will display an interaction that will make the tool move according to the inputted argument, so that the tool no longer needs assistance from humans and how to operate automatically or use the internet network for remote control. The implementation of IoT (Internet of Things) tools can also be carried out in the livestock sector, especially chicken farming, to control the situation in chickens in the form of: ammonia gas levels, water pH, temperature and humidity. In this study using the Fuzzy Tsukamoto logic algorithm method which is implemented on the IoT device to be made, the use of the Fuzzy Tsukamoto logic algorithm is very suitable for applying reasoning and the many rules that often change on the variables above